ORGANIZATION AND EVALUATION OF THE EDUCATIONAL PROCESS BASED ON EUTAGOGICAL APPROACHES - Khidirova, Malakhat (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article explores the implementation and assessment of educational practices rooted in eutagogy. Eutagogy, a learner-centered approach to education, emphasizes self-directed learning and individual autonomy. This article examines how eutagogical principles can be applied to organize and evaluate the educational process effectively. It discusses strategies for fostering learner engagement, personalized learning experiences, collaborative activities, and the integration of technology. The article also explores various assessment methods aligned with eutagogy, including formative assessments, authentic assessments, self-assessment, and peer assessment. By adopting eutagogical approaches, educators can create a conducive learning environment that promotes critical thinking, problem-solving, and lifelong learning skills in students.